Analisis Neraca Air dan Prasarana Tampungan Air di DAS Ciujung - Yulia Dwi Kurniasari; Hadi Susilo Arifin; Muhammad Yanuar Purwanto (School of Postgraduate Studies, Diponegoro Univer, 2021)
Peningkatan jumlah penduduk, laju pertumbuhan ekonomi dan pengembangan wilayah berdampak pada kondisi sumber daya air. Keterbatasan prasarana tampungan air menjadi penyebab pentingnya distribusi sumber daya air secara berkelanjutan. Penelitian ini bertujuan mengetahui kondisi neraca air dan prasarana tampungan air yang ada di DAS Ciujung. Metode yang digunakan adalah menghitung kebutuhan dan ketersediaan air, Neraca surplus-defisit, Indeks Pemakaian Air (IPA) dan Indeks ketersediaan air per kapita berdasarkan metode SNI 6728.1.2015 serta indikator tampungan air. Ketersediaan air dihitung berdasarkan debit andalan 80% (Q80). Kebutuhan air dihitung dari kebutuhan rumah tangga, perkotaan, industri (RKI), irigasi, peternakan, perikanan dan pemeliharaan sungai. Prasarana tampungan air dihitung melalui indikator tampungan bangunan konservasi air yang ada. Hasil analisis menunjukkan bahwa kebutuhan air di DAS Ciujung sebesar 37,52 m3/detik sedangkan ketersediaan airnya sebesar 36,57 m3/detik. Hal ini mengindikasikan adanya defisit air sebesar 0,95 m3/detik. Indeks Pemakaian Air sebesar 1,03 (kategori jelek). Indeks ketersediaan air per kapita sebesar 623,05 (indikasi kelangkaan air). Sedangkan indikator tampungan air sebesar 31,34% (kategori baik). ABSTRACTThe population growth, the rapid rate of economic growth and regional development will have an impact on the condition of water resources. Limited water storage infrastructure is the importance cause of allocating water resources. The objective of study is to know the water balance and water storage infrastructure in Ciujung Watershed. The analysis methods was used to calculate the amount of water supply and demand, to calculate the surplus-deficit balance, Water Consumption index (IPA), Water Availability Index per Capita refers to SNI 6728.1.2015 and water storage indicator. Water supply calculation based on the mainstay discharge of 80% (Q80). Water demands calculation from the demand of households, cities and industries (RKI), irrigation, livestock, fisheries and river maintenance. Capacity of existing water conservation storage used to predict the water storage infrastructure. The results of analysis show that the water demands in Ciujung Watershed is 37,52 m3/second, while the water supply is 36,57 m3/second. This indicates there is a water deficit of 0,95 m3/second. According to calculation, Water Consumption Index is 1,03 (bad category), It resulted that Water availability index per capita is 623,05 (water scarcity indicator). On the other hand, Indicator for water storage is 31,34% (good category).